Laboratory Animal PET/SPECT-CT Imaging for Biomedical Research (Journal of Laboratory Animal Science, 2024)
Small laboratory animal models are being increasingly used as a biomedical research tool in several human diseases such  as cancer, cardiovascular diseases, endocrine disorders and obesity. For the last couple of years, molecular and functional  imaging become a powerful techniques for studying spatial and temporal distribution of new drugs and their target  affinity non-invasively in animal models. Hence non invasive imaging modalities such as positron emission tomography  (PET), single photon emission computed tomography (SPECT), X-ray, magnetic resonance imaging, fluorescence and  bioluminescence have emerged for rapid and accurate screening of the new molecules. This review focuses on nuclear  imaging modalities mainly SPECT and PET, which allow whole body survey of the animal and quantitation of target  affinity. While establishing such facilities, accessibility to vivarium, work flow, availability of radiotracers, regulatory  requirements and trained human resource needs to be considered. The readout data requires dedicated software for viewing  and quantitation eg. VIVID, PMOD, AMIDE and Micro View. Therefore, a perfect amalgamation of instrumentation,  facility logistics and work flow that is required for efficiently managing such a facility has been elaborately reviewed in  this article.
Keywords: Small Animal Imaging; microPET; microSPECT; microCT; preclinical imaging